Analysis of supply chain management system using lean six sigma: Balanced scoredcard parameters approach - Prasetyo, Wahyu Eko (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
The potential development of the beauty product industry in Indonesia is considered very attractive. The beauty products industry and trade in Indonesia is projected to increase by USD 7.5 billion with a growth of 6.5% annually for the next five years. The huge potential in the cosmetics retail business is considered to trigger the emergence of competition, especially in the supply chain system which has implications for product affordability to consumers. So that this becomes an interesting condition for research to be carried out as well as efforts to provide certain improvement treatments so that there is an improvement in the flow of the supply system in the object company. In this study, 3 layers of the research process will be carried out, namely observing and describing the existing supply chain system in the research object company, improving and treating the supply chain system using a lean six sigma model with stages of define, measure, analyze, improve, control (DMAIC), and make observations as well as measure the results of improvement using 4 (four) balanced scoredcard performance indicators. Data mining using observation methods, interviews, scoring key performance indicators in each perspective, and study of company operational administration data. Based on the results of study, the supply system based on 4 balanced scoredcard indicators still has shortcomings, namely in the value of debt-to-equity ratio, quantity and customer quality, internal business organization, and personnel accountability. The recommendation is that this study can have an improving effect on the object company and also be a reference for other companies specifically with the same segmentation.